Moringa Leaf Infusion and Tea: How are Their Antioxidant Activities Different? - Irma Rahmawati; Sinta Dewi Anggraeni; Andi Ika Julianti (Elkawnie: Journal of Islamic Science and Technology, 2022)
Abstract: The global pandemic of the COVID-19 virus has made people around the world aware of the importance of maintaining health. Various efforts have been made to prevent the transmission of the COVID-19 virus, one of which is increasing the body's resistance. Moringa leaf (Moringa oleifera L.) is a medicinal plant that has properties that function as the main antiretroviral molecule to increase the activity of the immune system. This study aims to compare the antioxidant activity of Moringa leaf infusion and Moringa leaf tea. In this study, an analysis of antioxidant activity was performed using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Antioxidant activity of Moringa leaf infusion, Moringa leaf tea, and vitamin C as a comparison with IC50 values of 31.68 mg/mL; 31.17 mg/mL; 0.99 mg/mL. This is supported by the results of statistical tests which show that there are significant differences in the antioxidant activity of Moringa leaf infusion samples and Moringa leaf tea samples. It can be concluded that the antioxidant activity of Moringa tea is greater than Moringa leaf infusion.Abstrak: Pandemi global virus Covid-19, menyadarkan masyarakat di seluruh dunia terhadap pentingnya menjaga kesehatan. Berbagai upaya dilakukan untuk mencegah penularan virus Covid-19, salah satunya dengan meningkatkan daya tahan tubuh. Daun kelor (Moringa oleifera L.) merupakan tumbuhan obat yang mempunyai khasiat yang berfungsi sebagai molekul utama antiretroviral untuk meningkatkan aktivitas sistem kekebalan tubuh. Penelitian ini bertujuan untuk mengetahui perbandingan aktivitas antioksidan pada infusa daun kelor dan seduhan teh daun kelor. Pada penelitian ini, dilakukan analisis aktivitas antioksidan dengan metode DPPH (1,1-diphenyl-2-picrylhydrazyl). Aktivitas antioksidan pada infusa daun kelor, teh daun kelor, vitamin C sebagai pembanding dengan nilai IC50 berturut-turut sebesar 31,68 mg/mL; 31,17 mg/mL; 0,99 mg/mL. Hal ini didukung dengan hasil uji statistik yang menunjukan terdapat perbedaan aktivitas antioksidan yang signifikan dari sampel infusa daun kelor maupun sampel teh daun kelor. Berdasarkan hasil tersebut dapat disimpulkan bahwa aktivitas antioksidan teh daun kelor lebih besar daripada infusa daun kelor.